Social Agencies for Children and Families as Street Level Bureaucracies. A Case Study. - Fabio Cappello (Social Work and Society)
Social workers in public welfare services can be considered, according to Michael Lipsky theorization, street level bureaucrats. Lipsky (1980) defines as street level bureaucrats all public service workers who interact directly with citizens and have substantial discretion in the execution of their work. They are professionals who grant access to State programs and provide services within these programs; but they also operate in an environment where resources are chronically inadequate to the task they are asked to perform, where goals expectations tend to be ambiguous, conflicting or vague and where the demand for services tends to increase constantly to meet the supply. The working conditions of street level bureaucrats are unavoidably uncertain: they are regularly confronted with dilemmas that are not just ethical but also organizational. Due to this situation, discretion represents for them, simultaneously, a crucial tool to work with in very complicated situations - where the human dimension is essential - and an important option in order to solve or simplify the mentioned organizational contradictions. In the first case discretion may be synonymous of professional autonomy; in the second it may represent a strategy to cope with uncertainties and work pressures, often through the rationing of services (which may even mean autonomous reduction of the level of services).